PENGARUH E-WOM, PRICE DISCOUNT, ONLINE CUSTOMER REVIEW, DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA PLATFORM SHOPEE - Khaivi, Pelangi Dwi; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research aims to determine the influence of e-wom, price discounts, online customer reviews and online customer ratings on online purchasing decisions on the Shopee platform for undergraduate management students at Muhammadiyah University of Bengkulu. This type of research is a quantitative descriptive type of research, the object of this research is users of the Shopee application among Management undergraduate students at Muhammadiyah University of Bengkulu. The sampling method uses accidental sampling technique. The number of respondents in this study was 150 people. The data collection method uses a questionnaire. The data analysis technique uses the Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely the t test and f test. The results of this research can be concluded that the E-wom variable has a positive effect on Purchasing Decisions, Price Discount has a positive effect on Purchasing Decisions, Online Customer Review has a positive effect on Purchasing Decisions, Online Customer Rating has a positive effect on Purchasing Decisions, and E-wom, Price Discount , Online Customer Review, Online Customer Rating together have a positive and significant influence on online purchasing decisions on the Shopee platform for Bachelor of Management students at Muhammadiyah University of Bengkulu. Keywords: Electronic Word of Mouth, Price Discount, Online Customer Review, and Online Customer Rating, Purchase Decision